Method of Gene Construction Described - Eastman, Elke (1985)
The press release describes Applications Data Sheet DS-671 and the strategy for gene construction outlined therein.
Keywords: Marketing; Scientific apparatus and instruments; DNA--Synthesis; Beckman Instruments, Inc.